Houses in the Wood to enjoy the Sun and the Stars - Elena Mucelli (Agathón)
In 1938, Gio Ponti and Bernard Rudofsky worked out a project for a hotel in the woods in which architecture and landscape should blend into one in an endless toeing and froing whereby the indoor spills into the outdoor and the landscape breaks into the house. Based on Ponti’s original drawings, the author goes through the space of one of the hotel rooms by building a physical model of it. The photographs of the hotel, taken from the perspectives mentioned by the author and the angle argued from the general layout, are a way to understand the relationships between man, architecture and landscape, as suggested by the drawings and descriptions of the project.